The influence of rhythmic gymnastics on the students’ movement creativity levels - Fauzi, Muhammad Alief; Hermawan, Irwan; Arifin, Z.; Kosasih, Alam Hadi; Sonjaya, Azhar Ramadhana (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This research aimed to determine rhythmic gymnastics’ influence on students’ movement creativity in class VII MTSS Al Ma’arif Cilageni. In this case, movement creativity is defined as changes in body position that can stimulate students’ smoothness, flexibility, originality of thinking, detail orientation, and sensitivity. The research method employed was quantitative, particularly an ex post facto design. This study’s population was 25 students of class VII. The instruments covering questionnaires, observations, and documents were tested for validity and reliability to ensure accurate and reliable data. Data analysis was carried out using descriptive statistics, describing the average score and percentage of each component of movement creativity levels. The research results show that students’ movement creativity level is mostly in the medium category, namely 35%. The results indicate that the fluency and flexibility components needed to be improved, while the students’ authenticity, detail orientation, and sensitivity were quite good. This means that more effective rhythmic gymnastics learning model is necessary to increase students’ movement creativity, especially in terms of fluency and flexibility. The research results are expected to be valuable input for teachers to improve the quality of rhythmic gymnastics learning. Implementing the right learning model leads to more optimal and better movement creativity of students. Thus, it can support the development of their motor and cognitive skills.